THE EFFECT OF USING QUIZIZZ TO EFL STUDENTS’ ENGAGEMENT AND LEARNING OUTCOME - Ahmad Munawir; Nurul Pratiwi Hasbi (University of Kuningan, 2021)
The objectives of the research are to find out the extent of students' engagement in EFL learning before using Quizizz application, to find out students' score results from the test using Quizizz application, to find out the extent of students' behavior during the EFL learning and to find out the effect after using Quizizz to students' engagement and learning outcomes in EFL learning. This research applies a one-shot case study on explanatory quantitative research design to describe a phenomenon on the effectiveness of student engagement and learning outcomes after using Quizizz application in the EFL classroom of the 5th semester at the English Education Department in Universitas Sulawesi Barat. There are four classes and the researcher took one class purposively. The data are collected by employing preliminary and final surveys, treatments, direct observation, and tests. Structural equation modeling analyses show that using Quizizz application gave constructively contribution to some of the dependent variables. The effect of using Quizizz has the highest contribution or influence on the students' psychomotor outcomes. Next is to the effect of using Quizizz to the students' cognitive and affective outcomes. Moreover, student engagement is little or not significantly affected by the use of Quizizz. The conclusion highlights the importance, although currently ignored, ways that students contribute depends on the flow of the instruction they received. Moreover, the learning environment encourages students to think. As a concern to the teacher that students need motivational elements than a scoring system to increase their motivation.